FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN MEMBELI MOBIL MEREK TOYOTA TIPE KIJANG INNOVA PADA PT. DUNIA BARUSA BANDA ACEH - Suryani Murad; Redi Yusdia (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
This research empirically excamines the influence of decision of consumer about to purchase of brand car Toyota Kijang Innova in PT. Dunia Barusa Banda Aceh. The aim of this research is to find out the influence of cultural, social, personal and psychologist factor toward the decisions of consumen purchase in buying of brand car Toyota Kijang Innova in PT Dunia Barusa Banda Aceh.Collecting data is conducted by giving questionnaires to consumen owner of Kijang Innova car which choosed conveniencely in serving area of purna selling in PT. Duni Barusa Banda Aceh. This analysis uses multiple linear regression with SPSS. It influences culture, social, personal and psychology factors partially toward consumen decision in purchasing of brand caa Kijang Innova significant with t-table (1.9842) in significant level of for each them is 0.005, 0.000 and 0.014 or it’s smaller than 0.005. It’s influenced all factors of independent variable simoultaneously toward dependent variable that it’s also significant with F-test(110.007)F-table(2.4675). The relation of independent variable with dependent variable positively with R value 90.70%. The influence of four factors in decision of purchasing of brand car Kijang Innova is R2 value 0,822 that means 82.20% changing dependent variable can explain by independent variables. The rest of that value, which is 17.80% can explain by other variables outside model.Keywords: consumer, purchase, cultural, social, personal, psychologist